1990
DOI: 10.1172/jci114592
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of myocardial contractile depression by clinical concentrations of ethanol. A study in ferret papillary muscles.

Abstract: Moderate alcohol intoxication in man, a ubiqitious social event, causes acute but reversible myocardial depression, the mechanism of which is unknown. We investigated whether this depression could be due to a direct effect of ethanol on the process of electromechanical coupling by simultaneously measuring the transmembrane action potential and contraction, or the cytosolic calcium transient (via aequorin photoluminescence) and contraction in isolated ferret right ventricular papillary muscle. Ethanol, in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…The hallmarks of alcoholic cardiomyopathy are altered cardiac contractile function and impaired intracellular Ca 2ϩ mobilization such as decreased SR Ca 2ϩ function, which may underlie the altered cardiac mechanics (2,3,8,24,29,30). It is postulated that inhibition by ethanol of Ca 2ϩ regulatory proteins such as Ca 2ϩ pumps and channels may play a role in the decreased cytosolic Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmarks of alcoholic cardiomyopathy are altered cardiac contractile function and impaired intracellular Ca 2ϩ mobilization such as decreased SR Ca 2ϩ function, which may underlie the altered cardiac mechanics (2,3,8,24,29,30). It is postulated that inhibition by ethanol of Ca 2ϩ regulatory proteins such as Ca 2ϩ pumps and channels may play a role in the decreased cytosolic Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol (ethanol) ingestion leads to impaired cardiac function, including depressed cardiac contraction, ventricular hypertrophy and electrophysiologic abnormalities [3,5,9,16]. Moreover, excessive ethanol may be associated with alcoholic cardiomyopathy, a clinical condition that leads to ventricular dysfunction, hypertension and heart failure [2,29].…”
mentioning
confidence: 99%
“…Although ethanol has been reported to both improve and impair cardiac function in human and experimental animals, it depresses contractile function unequivocally in isolated cardiac preparations [1,[3][4][5]8]. Recent studies suggested that changes at the single cardiac myocyte level, such as myofibril Ca 2+ sensitivity, plasma membrane properties and intracellular Ca 2+ , are responsible for ethanol-induced myocardial alteration [5,9,18,25].…”
mentioning
confidence: 99%
“…These studies have demonstrated that ethanol has multiple effects on the myocardium, and as such could depress the force of contraction at several points in the process of electromechanical coupling, probably at the level of the myofilaments. The effect was found to be reversible by increasing the amount of calcium presented to the myofilaments or by washing out the ethanol (Guarnieri and Lakatta 1990). This cardiodepresive action of ethanol is evidenced in experimental models designed with autonomic blockade, heart denervation, or isolated cells.…”
Section: Alcoholmentioning
confidence: 88%
“…it has a direct negative inotropic action with a reversible dose-dependent decrease in myocardial contractility. Most studies of isolated myocardium have sought to explain these acute and reversible changes in the force of contraction by using pharmacologic concentrations of ethanol in the 1% (by volume) range (Knochel 1983;Guarnieri and Lakatta 1990). These studies have demonstrated that ethanol has multiple effects on the myocardium, and as such could depress the force of contraction at several points in the process of electromechanical coupling, probably at the level of the myofilaments.…”
Section: Alcoholmentioning
confidence: 99%